Grundtvig og fundamentalismen - Pedersen, Kim Arne (Grundtvig-Studier, 2005)
Grundtvig og fundamentalismen [Grundtvig and fundamentalism] By Kim Arne Pedersen The chosen starting-point is Ole Vind’s perception of Gr as a Biblefundamentalist. Vind constructs a concept of fundamentalism along idea-historical lines and focuses on what he perceives to be Gr’s literal reading of, especially, the Old Testament; but he also emphasises that for Gr the Scriptures were directly inspired by God. Through the introduction of a theological-historical and secularhistorical definition of the concept of fundamentalism, Gr’s relationship to the Bible is examined with the aim of mounting a critique of Vind’s interpretation. Gr’s view of the Bible in the period 1810-11 to 1824-25 is characterised against the background of that struggle with himself which his conversion in 1810 entailed, and with the introduction of the theological-historical definition of fundamentalism. This finds its starting-point in fundamentalism as a concrete historical phenomenon in the USA at the end of the 19th and beginning of the 20th century. It is distinguished by the resolution of traditional Christianity into five dogmatic points, including the dogma of verbalinspiration (every word in the Holy Scriptures is divinely dictated), to which is added the individual Christian’s personal inner experience with its basis in conversion. With this as background, Gr may be called fundamentalist in the period 1810 to 1824-25, since Gr (1) has been through a more or less pietistic conversion, (2) rejects a historical-critical approach to the Bible, (3) holds firm to verbal-inspiration, (4) rejects a modem interpretation of Christianity, (5) holds firm to traditional Christianity against the rationalists and would certainly have been able to subscribe to the fundamentalists’ five points, (6) rejects a scientific explanation of the world, and (7) believes that a form of scientific alternative to the world-picture of the natural sciences can be worked out on a Biblical basis. However, the theological-historical definition of fundamentalism needs to be supplemented by a secular-historical determination of the concept. Here a link is made with Uffe Østergaard’s demonstration of the significance of the art of printing in the Reformation as a prerequisite of fundamentalism, in that verbal-inspiration is thus placed centre-stage. Østergaard’s point is that fundamentalism is not only a reaction against modernisation, but is itself a modem phenomenon, and here he focuses upon the fundamentalists’ insistence upon a direct access to Scripture independently of religious tradition’s mediating influence. Here Østergaard’s observations are supplemented by the viewpoint that the revivalist movements of the 18th and 19th centuries are the foundation of fundamentalism; and the German concept-historical school’s concept of modernity is introduced, supplemented by Habermas’s Kant-inspired determination of subjectivity as the core of modernity, and of secularisation as a consequence of the differentiation of spheres of validity it entails. Finally, it is proposed that fundamentalism in a secular-historical sense must be seen as a consequence of secularisation as an historical phenomenon, affected by industrialisation and the dominance of the natural sciences after 1850. Thus fundamentalists belong in the period after 1850 as the second phase of modernisation, and they seek to direct society back to an idealised golden age. The core of the theological-historical definition of fundamentalism is the conflict between traditional religion and a modem interpretation of it; the core of the secular-historical definition is the conflict between modernisation/secularisation and a religious reaction against this, which desires the whole of society or a state within the state free of secularisation. After Gr’s struggle with aspects of his understanding of Christianity in 1824-25 his view of the Bible becomes freer and he breaks explicitly with the dogma of verbal-inspiration. However, Gr’s location in time itself, and his complex attitude towards modernity is of more importance. (1) Gr can hardly be lumped together with that group of modem intellectuals, people with education, who are related to industrial and post-industrial society and who are going through a fundamentalist conversion. Grundtvig belongs in another age, in modernity’s first phase from 1750 to 1850 - and his concept of modernity can be extrapolated from analyses of his complex attitude towards Kant’s concept of autonomy. The facts that (2) between 1811 and 1824 he is an adherent of verbal-inspiration, and (3) in his battle with Enlightenment theology (and in that connection with the ecclesiastical authorities) he turns against the traditional theological teaching institutions, and (4) he wishes to reform theology, are not sufficient grounds for characterising him as a fundamentalist, for Gr (5) does not want, as do the fundamentalists, a return to an idealized golden age. In Gr’s notion of the sequence of national congregations, and the fact that the one succeeds to the other, lies hidden a historical mentality stamped with the idea that the different congregations embody different characteristics. To conceptualise change is modem, and in that sense Gr is stamped with modernity. (7) Ultimately, Gr does not seek to stifle the scientific attempt to clarify the Bible and the world independently of a literal reading of the Old Testament. This Vind overlooks, when he alleges that even after 1825 Gr can be called a fundamentalist. The decisive characteristic which divides Gr from fundamentalism is really not his break with Bible-Christianity in 1823, 1824 and 1825, nor his related rejection of verbal-inspiration, but rather the opening of his mind in relation to the naturalists, and therewith the theologicallyorientated foundation of this opening upon two central concepts: his educational idea - that is, the separation between church and school - and his idea of freedom. The educational concept and the concept of freedom are indissolubly bound together, and Gr’s thematising of freedom in respect of things scientific is tied up with his consciousness of modernity.